Electroosmotic pump‐supported molecularly imprinted monolithic column for capillary chromatographic separation of nitrophenol isomers. Issue 23 (30th October 2015) - Wu, Yue; Zhang, Wenpeng; Chen, Ying; Chen, Zilin
Abstract : In this work, a novel molecularly imprinted polymer (MIP) monolithic column with integrated in‐column electroosmotic pump (EOP) was designed and successfully prepared to facilitate the capillary chromatography with MIP column. A silica‐based EOP was synthesized at the detection end of the MIP monolithic capillary column by so‐gel to provide the hydrodynamic driven force for the capillary chromatography. Because of large surface area and low fluidic resistance of the silica monolith, a strong and steady EOF was generated by silica‐based EOP, indicating that the EOP was quite compatible with MIP capillary column. With the sufficient EOF provided by EOP, the electro‐driven based capillary chromatographic separation of nitrophenol isomers was achieved in 4‐vinylpyridine‐based MIP monolithic capillary, which was originally proved infeasible because of the EOF shortage. No significant influence upon the specific recognition of the MIP was found due to the setting of EOP after the detection window of the column. The influence of experimental parameters on the EOF such as voltage and pH value of running buffer was investigated. The column was also evaluated by capillary liquid chromatographic mode to compare with EOP‐driven capillary chromatography. Higher column efficiency was obtained by EOP‐driven separation with improved peak shape. The results suggested that EOP‐supported technique would be a good way to solve the problem of weak EOF generation in electro‐driven capillary chromatography.